Selff Assessment sebagai Praktik Baik Menyiapkan Akreditasi Perpustakaan - Hariyah Hariyah (UIN Imam Bonjol Padang, 2019)
Building a professional library can be cultivated one of them through the application of library standards. In practice the application of library standards is not always easy especially in the framework of library accreditation.This paper raises the experience of libraries in the Research and Development and Training Center of the Ministry of Religious Affairs, namely namely the Manado Religious Training Center Library and the Lajnah Pentashihan Mushaf Al-Qur’an Library in conducting self assessment using library standards. The instrument used to conduct the self assessment is entirely taken from the Indonesian National Standard for Special Libraries of Government Agencies with additional modifications that are adapted to the state of the library. The instruments featured in this paper include the functions of libraries, collections, organizing library materials, human resources, managers, library services, library organizations, buildings, equipment, budgets, and information and communication technology.